ChemInform Abstract: Three New Abietane‐Type Diterpenes from the Bark of Cryptomeria japonica. Issue 52 (6th December 2016) - Chang, Chi‐I; Chen, Chien‐Chih; Wang, Sheng‐Yang; Chao, Che‐Yi; Chao, Louis Kuoping; Chen, Jih‐Jung; Ko, Horng‐Huey; Chen, Cheng‐Chi; Kuo, Yueh‐Hsiung
Abstract: isolation and structure elucidation